Do 401k plan advisors take their own advice?. (24th February 2014) - DVORAK, TOMAS
Abstract: Sponsors of defined contribution plans often hire financial advisors to help them design and monitor their plans. I find that advisors have a significant impact on the menu of investment options of their clients' plans. Clients of the same advisor tend to hold the same funds and fund families. They also tend to delete and add the same funds. Advisors' plans are similar to their clients' plans in that they tend to hold identical funds, use the same fund families, and fund categories. Thus, to a large extent, advisors take their own advice. However, funds that are in clients' plans but not in their advisors' plans have higher expense ratios than the funds held by advisors. Since advisors' compensation is often tied to the expense ratio of their clients' funds, this pattern is consistent with misaligned incentives on the part of advisors and their clients.